Increasing wildfire impacts on snowpack in the western U.S - Kampf, Stephanie K; McGrath, Daniel; Sears, Megan G; Fassnacht, Steven R; Kiewiet, Leonie; Hammond, John C (Proceedings of the National Academy of Sciences - PNAS, 2022)
Wildfire area has been increasing in most ecoregions across the western United States, including snow-dominated regions. These fires modify snow accumulation, ablation, and duration, but the sign and magnitude of these impacts can vary substantially between regions. This study compares spatiotemporal patterns of western United States wildfires between ecoregions and snow zones. Results demonstrate significant increases in wildfire area from 1984 to 2020 throughout the West, including the Sierra Nevada, Cascades, Basin and Range, and Northern to Southern Rockies. In the late snow zone, where mean annual snow-free date is in May or later, 70% of ecoregions experienced significant increases in wildfire area since 1984. The distribution of burned area shifted from earlier melt zones to later-melt snow zones in several ecoregions, including the Southern Rockies, where the area burned in the late snow zone during 2020 exceeded the total burned area over the previous 36 y combined. Snow measurements at a large Southern Rockies fire revealed that burning caused lower magnitude and earlier peak snow-water equivalent as well as an 18-24 d estimated advance in snow-free dates. Latitude, a proxy for solar radiation, is a dominant driver of snow-free date, and fire advances snow-free timing through a more-positive net shortwave radiation balance. This loss of snow can reduce both ecosystem water availability and streamflow generation in a region that relies heavily on mountain snowpack for water supply.